Survival of children treated for Ewing sarcoma in Lithuania: a single centre experience - Jakutis, Gabrielius; Ragelienė, Lina; Rascon, Jelena (Acta medica Lituanica, 2018)
Introduction. Ewing sarcoma (ES) is a rare and aggressive malignant neoplasm that mostly affects children and adolescents. Recent studies reported a gap of 20% in childhood cancer survival rates between the Northern/ Western and the Eastern European countries. We aimed to analyse the survival of patients treated for ES at our institution, to evaluate its correspondence to current survival rates in the expert centres, and to assess changes in treatment outcomes over time. Materials and methods. A retrospective single-centre study was performed. Children under 18 years of age, diagnosed and treated for Ewing sarcoma/PNET at our institution from 2000 to 2014 were included. To assess the hypothesized improvement of treatment outcomes over time, a comparative analysis of two time periods – 2000–2007 and 2008–2014 – was carried out. Five-year overall survival (OS5y) and disease-free survival (DFS5y) were chosen as primary study end-points. Clinical and laboratory data were retrieved from patient records. Results. In total, 40 patients were included in the study: 24 (60%) males and 16 (40%) females. Twenty-eight children (70%) presented with local and 12 (30%) with primary metastatic disease. Over the analysed time frame, improvement in treatment outcomes was observed: DFS5y improved from 46% in 2000–2007 to 61% in 2008–2014 (p = 0.27), whereas OS5y changed minimally from 62% in 2000–2007 to 65% in 2008–2014. Increase in DFS5y was more prominent for localized disease –from 50% in 2000–2007 to 74% in 2008–2014 (p = 0.14). Prognosis of initial metastatic disease remained poor with DFS5y: 25% in 2000–2007 and 38% in 2008–2014. Patients’ median follow-up was 12.3 years (the range from 8.1 to 15.6) and 3.9 years (the range from 1.1 to 8.0) in the first and second study groups, respectively. Conclusions. OS5y of the entire patient cohort did not change considerably over time and remained slightly inferior compared to the best reported survival rates. There was an evident trend for improvement of DFS5y in localized disease. Survival of children with primary metastases remained poor despite slight increase in DFS5y. Implementation of international clinical trials, consolidation of multidisciplinary approach, patients’ concentration and widening of research activities could be beneficial for the treatment of children in the future.